STRATEGI PENDIDIKAN UNTUK SUKSES DI ERA TEKNOLOGI 5.0 - Fricticarani, Ade; Hayati, Amalia; R, Ramdani; Hoirunisa, Irva; Rosdalina, Gina Mutiara (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
Technology 5.0 is the latest evolution of technology, connecting the physical and digital worlds in a more integrative and effective way from its definition to its application in various sectors such as manufacturing, agriculture, health, and education. In the era of technology 5.0, technology optimizes human life by accelerating production processes and providing more efficient and accurate solutions. However, technological development also brings challenges, such as the irresponsible use of technology and privacy violations. The era of Technology 5.0 is a new phenomenon in technology development in various fields, including education. This change affects education to develop competencies and skills for the 21st century. This article reviews the development of education in the era of Technology 5.0, as well as the challenges and opportunities related to the use of technology in education. In this era, technology-based curricula and learning methods must be developed to meet the needs of the times. Teachers also need to be trained to have the ability to operate increasingly sophisticated technology and to take advantage of opportunities to create more inclusive and skill-based learning. Education in the era of Technology 5.0 provides an opportunity to strengthen the relevance of education to the needs of the times.